2013
DOI: 10.1103/physrevb.87.214505
|View full text |Cite
|
Sign up to set email alerts
|

Upper limit of metastability of the vortex-free state of a two-dimensional superconductor in a nonuniform magnetic field

Abstract: We calculate the magnetic field above which vortices necessarily appear in a two-dimensional superconducting film in a non-uniform magnetic field applied near its center, as in two-coil measurements of superfluid density. Experiments suggest that free vortices appear when the Meissner screening current density is large enough that the free-energy barrier for separating tightly-bound vortex-antivortex (V-aV) pairs into free vortices is comparable to k B T , not at the much lower thermodynamic critical field. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…We have empirically identified the applied driving magnetic field associated with vortex-antivortex pairs unbinding en masse in the films, informed by a microscopic model which includes flux pinning. Our data on eight films fit well to Lemberger and Ahmed's recent calculation of the upper bound of the vortex-free state as a function of superfluid density 7 , and we are able to extract values of the superconducting coherence length from these data in quantitative agreement with values measured from the films' upper critical fields.…”
Section: Discussionsupporting
confidence: 82%
“…We have empirically identified the applied driving magnetic field associated with vortex-antivortex pairs unbinding en masse in the films, informed by a microscopic model which includes flux pinning. Our data on eight films fit well to Lemberger and Ahmed's recent calculation of the upper bound of the vortex-free state as a function of superfluid density 7 , and we are able to extract values of the superconducting coherence length from these data in quantitative agreement with values measured from the films' upper critical fields.…”
Section: Discussionsupporting
confidence: 82%
“…The actual applied field (or field coil current) at which nonlinearity due to vortex dynamics begins to occur is necessarily smaller than this maximum vortex-free field, which is consistent with the SQUID measurements (Figure 2 (f)). In a homogeneous 2D superconductor, vortices are expected to first appear at the position with the highest superfluid momentum, i.e., the position where the vector potential |A(r)| is largest [47,49], and we expect the same to be true for the ordered array. Any vortices that are present will experience a force due to the local AC applied field from the field coil.…”
Section: Resultsmentioning
confidence: 95%
“…One candidate is motion of vortices induced in the 2D superconducting system above a lower critical field B crit 0 , as has been studied theoretically for uniform applied fields [44,45] and for nonuniform applied fields in the context of two-coil mutual inductance susceptibility measurements [46][47][48]. Lemberger and Ahmed [47] found that for a 2D superconductor in the weak screening (large Λ) limit with Ginzburg-Landau coherence length ξ subject to a nonuniform field from a point dipole or small current loop, there can be no vortex-free state above a lower critical field B crit 0 ≈ Φ 0 /(2ρ 0 ξ), where ρ 0 Λ is the radial distance from the magnetic source at which the applied field changes sign. This relationship between the coherence length ξ and the onset of vortex-related nonlinear magnetic response has been used to measure ξ in superconducting thin films [48].…”
Section: Resultsmentioning
confidence: 99%
“…The critical pair momentum p c is computed from the lowtemperature values of B NL by a calculation of Lemberger and Ahmed [12] using an idealized version of our experimental configuration. We report values of p c for our cuprate films using this result, assuming that the measured B NL coincides with the applied field at which the Meissner state is becomes unstable, and vortex-antivortex pairs unbind en masse [13].…”
mentioning
confidence: 99%